please answer.....
![{cot}^{2} a( \frac{sec \: a - 1}{1 + sin \: a}) + {sec}^{2} a( \frac{sin \:a - 1}{1 + sec \: a} ) = 0 {cot}^{2} a( \frac{sec \: a - 1}{1 + sin \: a}) + {sec}^{2} a( \frac{sin \:a - 1}{1 + sec \: a} ) = 0](https://tex.z-dn.net/?f=+%7Bcot%7D%5E%7B2%7D+a%28+%5Cfrac%7Bsec+%5C%3A+a+-+1%7D%7B1+%2B+sin+%5C%3A+a%7D%29+%2B++%7Bsec%7D%5E%7B2%7D++a%28+%5Cfrac%7Bsin+%5C%3Aa+-+1%7D%7B1+%2B+sec+%5C%3A+a%7D+%29+%3D+0)
Answers
Answered by
0
cot²A(secA-1/1+sinA)+sec²A(sinA-1/1+secA)
=cot²A[(secA-1)(1-sinA)/(1+sinA)(1-sinA)]+sec²A[(sinA-1)(secA-1)/(secA+1)(secA-1)]
=cot²A[(secA-secA.sinA-1+sinA)/(1-sin²A)]+sec²A[(sinA.secA-sinA-secA+1)/(sec²A-1)]
=cot²A[(secA-secA.sinA-1+sinA)/cos²A]+sec²A[(sinA.secA-sinA-secA+1)/tan²A]
=(cos²A/sin²A)[(secA-secA.sinA-1+sinA)/cos²A]+[sec²A(sinA.secA-sinA-secA+1)](cos²A/sin²A)
=[(secA-secA.sinA-1+sinA)/sin²A]+[(sinA.secA-sinA-secA+1)/sin²A]
=(secA-secA.sinA-1+sinA+sinA.secA-sinA-secA+1)/sin²A
=0/sin²A
=0
R.H.S=L.H.S
Similar questions